2014
DOI: 10.2298/apt1445033h
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of antioxidant and antimicrobial activity of chitosan film with caraway and oregano essential oils

Abstract: In this work, caraway or oregano essential oils were added to the cast chitosan film in an attempt to design a natural, biodegradable, bioactive (antioxidant and antimicrobial) packaging film. When the structure of the tested films was analyzed with Fourier transform infrared spectroscopy, no significant differences were found between the chitosan film with and without essential oils of caraway or oregano. The lowest antioxidant activity, based on the scavenging of the stable DPPH? free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The most dominant was chitosan spectra with typical peaks. In the following paragraphs are presented the main characteristic peaks of chitosan (Leceta et al, 2012;Hromiš et al, 2014) and changes caused by incorporating CEO into chitosan film.…”
Section: Visual Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The most dominant was chitosan spectra with typical peaks. In the following paragraphs are presented the main characteristic peaks of chitosan (Leceta et al, 2012;Hromiš et al, 2014) and changes caused by incorporating CEO into chitosan film.…”
Section: Visual Examinationmentioning
confidence: 99%
“…Those results are in line with results obtained in the present study for incorporation of CEO at the level of 2% and 3%, where no significant difference in scavenging activity was observed after 24 h. The results of this study also suggest that the concentration increase is reflected in faster activity achievement and that there is a capacity for oil incorporated in chitosan matrix to be released from chitosan film with the time, but that remaining oil rapidly migrates to the surface of the film and in the solution of DPPH. Hromiš et al (2014) investigated influence of storage time on antioxidant activity of chitosan film with 1% of CEO and results revealed that storage did not affect AO of this film after one month.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Oregano is a popular culinary herb with high content in EOs containing terpenoids, mainly the monoterpenoid phenols of thymol (5-methyl-2-[1-methylethyl] phenol) and carvacrol (5-isopropyl-2-methyl phenol) 50 . One important feature of the EOs obtained from oregano is their high antimicrobial activity, which is usually determined by the agar plate diffusion method, where the inhibition on solid media was used to determine the antimicrobial effects of active films against different bacteria 26 54,55 . Results showed positive inhibition for EOs concentrations higher than 5 % (w/w) for all bacteria 27,54,55-52 .…”
Section: Herbsmentioning
confidence: 99%
“…Increasing consumer awareness and health consciousness, however, has resulted in pressure to avoid utilising synthetic additives, which necessitates the use of natural additives to extend shelf-life and improve product safety (Descalzo and Sancho, 2008;Wojciak et al, 2011;Velasco and Williams, 2011;Savanovic et al, 2014a). The exploration and application of natural products that have antioxidant and antibacterial activities in meat products could be desirable and very useful to extend their storage shelf-life and perhaps aid in prevention of foodborne diseases (Hromis et al, 2014;Kumar and Tanwar, 2011;Abdel-Salam et al, 2014). Sources of natural antioxidants usually are spices, herbs, teas, oils, seeds, cereals, cocoa shell, grains, fruits and vegetables (Mata et al, 2007;Karabacak and Bozkurt, 2008;Opara and Al-Ani, 2010;Maciel et al, 2011;Ozvural et al, 2016).…”
Section: Introductionmentioning
confidence: 99%